2014
DOI: 10.1016/j.proeng.2014.11.765
|View full text |Cite
|
Sign up to set email alerts
|

Non-newtonian Mixed Convection Flow from a Horizontal Circular Cylinder with Uniform Surface Heat Flux

Abstract: Mixed convection laminar two-dimensional boundary-layer flow of non-Newtonian pseudo-plastic fluids is investigated from a horizontal circular cylinder with uniform surface heat flux using a modified power-law viscosity model, that contains no unrealistic limits of zero or infinite viscosity; consequently, no irremovable singularities are introduced into boundary-layer formulations for such fluids.. The governing boundary layer equations are transformed into a non-dimensional form and the resulting nonlinear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…En este sentido diversos autores estudian la dependencia de la transferencia de calor respecto al índice de comportamiento "n" [6][7][8][9][10][11][12]. Matin M.H.…”
Section: Agradecimientosunclassified
See 1 more Smart Citation
“…En este sentido diversos autores estudian la dependencia de la transferencia de calor respecto al índice de comportamiento "n" [6][7][8][9][10][11][12]. Matin M.H.…”
Section: Agradecimientosunclassified
“…Rao [10] determinan experimentalmente un comportamiento similar para el Nusselt en función de "n", en este caso el estudio de la convección forzada se realiza en un cilindro a contraflujo. En el caso de la convección mixta, Chandra [11] realiza un estudio de la convección alrededor de un semicilindro para un flujo asistido, en el que el índice de comportamiento es contemplado a través del número de Reynolds modificado, los resultados muestran que el número de Nusselt crece en relación al incremento del número de Reynolds mientras, el coeficiente de arrastre se incrementa respecto al aumento del número de Richardson, Para valores de Ri cercanos a la unidad la convección mixta es el mecanismo de transferencia de calor que predomina [11,12], en este sentido Bhowmick,et al,[11] presenta un estudio numérico de la convección mixta en un flujo asistido alrededor de un cilindro para un fluido no Newtoniano con valor del coeficiente de comportamiento, n = 0.6, compara sus resultados para el numero de Nusselt contra el valor de un fluido Newtoniano.…”
Section: Agradecimientosunclassified
“…The authors concluded that the nanofluid with non-Newtonian base is more stable and the density of nanoparticles also stabilizes the nanofluid layer. The laminar flow of non-Newtonian fluid around a circular cylinder with uniform heat dissipation was investigated by Bhowmick et al (2014). As a result, it was found that the temperature of the pseudoplastic fluid ( n = 0.6) actively decreases at the leading edge, whereas in the entire flow region it occurs more slowly.…”
Section: Introductionmentioning
confidence: 99%